Features of ergonomics of the CRT field of electronic textbooks for the system of vocational education - Yurzhenko, Volodymyr (Professional Pedagogics, 2012)
The article reveals essence of realization of content-ground in an environment programmatic instru- mental platform of MOODLE of educational objects which are used for training on workings professions in vocational education and the use of elements of method of the neuro-linguistic programming.